Nutritional and antioxidant property of non-conventional food plants (PANCs) and use in eating habits: review - Picinato Gomes, Julia; Silva De Oliveira , Paulo Henrique (Seven Editora, 2023)
Considering the nutritional potential and antioxidants of non-conventional food plants (PANCs) and seeking to minimize the environmental impact caused by waste residues of fruits and vegetables. The present study aimed to demonstrate its nutritional potential while inserted in the diet as a function of its nutritional and antioxidant constituents that, as a rule, are dumped by food industries on the planet. After analysis of the results of the research referenced in this review article, the information of four species (Portulaca oleracea L., Basella alba L.  Syn and B. rubra;  Lanata Stachys;  Xanthosoma saggitifolium) of unconventional food plants (PANCs), being a documentary analysis research. According to the results obtained by the aforementioned researchers, Basella alba L.  Syn and B. rubra;  Portulaca oleracea L.;  Stachys lanata, and Xanthosoma saggitifolium keep medicinal use, cytotoxicity and toxicity and food use of these species. Therefore, it should be concluded that non-conventional food plants (PANCs) should be significantly used. DOI: https://doi.org/10.56238/tfisdwv1-049